2015
DOI: 10.1021/acs.est.5b01145
|View full text |Cite
|
Sign up to set email alerts
|

Charge, Size, and Cellular Selectivity for Multiwall Carbon Nanotubes by Maize and Soybean

Abstract: Maize (Zea mays) and soybean (Glycine max) were used as model food-chain plants to explore vegetative uptake of differently charged multiwall carbon nanotubes (MWCNTs). Three types of MWCNTs, including neutral pristine MWCNT (p-MWCNT), positively charged MWCNT-NH2, and negatively charged MWCNT-COOH, were directly taken-up and translocated from hydroponic solution to roots, stems, and leaves of maize and soybean plants at the MWCNT concentrations ranging from 10.0 to 50.0 mg/L during 18-day exposures. MWCNTs ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…Wild and Jones [169] demonstrated that MWCNTs with a diameter of 110-170 nm could pierce the epidermal cell wall and thus penetrate up to 4 μm into the cytoplasm of wheat (T. aestvcum) root hairs. MWCNTs taken up by plant roots were even detected in the xylem and in phloem cells [129]. A root to shoot translocation of MWCNTs is most probably driven by transpiration [170] as demonstrated for wheat (T. aestivum) and rapeseed (B. napus) [171].…”
Section: Plant Cell Culturementioning
confidence: 93%
See 2 more Smart Citations
“…Wild and Jones [169] demonstrated that MWCNTs with a diameter of 110-170 nm could pierce the epidermal cell wall and thus penetrate up to 4 μm into the cytoplasm of wheat (T. aestvcum) root hairs. MWCNTs taken up by plant roots were even detected in the xylem and in phloem cells [129]. A root to shoot translocation of MWCNTs is most probably driven by transpiration [170] as demonstrated for wheat (T. aestivum) and rapeseed (B. napus) [171].…”
Section: Plant Cell Culturementioning
confidence: 93%
“…max.) seedlings [129]. Challenges related to TEM comprise low contrast between CNMs and plant tissue structures [130,151], a complicated sample preparation and the need for analysis of large numbers of samples.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, CNT exposure to terrestrial plants is likely. CNTs accumulated by crops could bioaccumulated and biomagnify along the food chain, eventually leading to human exposure [8][9][10][11][12][13][14][15]. Since CNTs may pose a significant risk to ecological and human health, it is essential to understand their toxicity, uptake, and translocation of CNTs in plant [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…No accumulation was reported in the roots of cabbage [20], carrot [20], cucumber [20], lettuce [20], onion [20], tomato [20], Alfalfa [21] and wheat [21]. However, CNTs uptake by maize [15], soybean [15], pea [11], sunflower [11], tomato [11], wheat [11,12], rapeseed [12] and different plant cells [8-10, 13, 14] was observed. Notably, most of these studies only used qualitative methods such as Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Raman spectroscopy [8-10, 13-15, 20, 22-25].…”
Section: Introductionmentioning
confidence: 99%